Legal Implications of the Determination of Roya Which is Not Accompanied by a Certificate of Full Payment (Study of Decision Number 594/Pdt.P/2023/Pn. Jkt Tim) - Sinaga, Hasudungan; Tri Bawono, Bambang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
A mortgage is a security right over land or buildings granted to a creditor as collateral for a debt owed by the debtor. In practice, the elimination of mortgage rights is a frequently encountered problem. One way to eliminate mortgage rights is through the roya process, a request for a roya determination due to the creditor's inability to provide a certificate of settlement, which is one of the main obstacles in the process of releasing mortgage rights over collateral objects. The expected objectives of this study are to determine and analyze the procedures for implementing a roya determination for the elimination of mortgage rights, as well as to determine and analyze the legal implications of a roya determination without a Certificate of Settlement. This study is expected to provide a clearer picture of the obstacles, both from a legal and administrative perspective, that may exist. In addition, it is also expected to contribute to the development of mortgage law in Indonesia in general. The research method used is Normative Juridical with a case analysis approach as one of its instruments and a normative approach method that focuses on normative legal analysis. It was found that the Court's decision ordering the National Land Agency to remove roya was to ensure the restoration of the Debtor's rights to the collateral submitted to the Creditor, the obstacles faced by the Debtor in the process, and provided recommendations to improve the effectiveness of the implementation of the court's authority to ensure legal certainty for Debtors who had paid off their debts. The results of the study indicate that although the court has the authority to handle roya applications, delays in the legal process and administrative obstacles at the National Land Agency often slow down the provision of legal certainty needed by Debtors.